(untitled) (Journal of Mathematical Study, 2014)
In this paper, we are concerned with the properties of positive solutions of the following nonlinear integral systems on the Heisenberg group H^n, equation {arrayll u(x)=_H^nv^q(y)w^r(y)|x^-1y|^α|y|^β dy, v(x)=_H^nu^p(y)w^r(y)|x^-1y|^α|y|^β dy, w(x)=_H^nu^p(y)v^q(y)|x^-1y|^α|y|^β dy, array.equation for xH^n, where 0